(untitled) (Nepal Medical College Journal, 2025)
Laparoscopic pyeloplasty is preferred surgery to treat patients with Pelvi-ureteric junction obstruction(PUJO). The main objective of the study was to assess outcome of laparoscopic pyeloplasty in our university hospital. This was retrospective descriptive observational study which included 36 patients diagnosed with PUJO by CT IVU (intravenous urography) and diuretic DTPA (Diethylenetriamine Pentaacetic acid) renogram presented to Dhulikhel hospital from 1st January 2023 to 30th January 2025. Patient were reviewed in terms of demographic characteristics, clinical presentation and radiological findings. Statistical correlation with the presence of crossing vessels was analyzed using student’s t-test and Fisher’s exact test. Mean age was 30.03±10.66 years, 17(47.22%) female and 19(52.78%) male patient. Most of the patient were asymptomatic 38.89% followed by pain 33.33%. crossing vessel compression was noted in 10 patient(27.78%). Mean operative duration was 174.17±18.80 minutes. Mean hospital stay was 2.67±0.48 days. A statistically significant correlation was noted between the presence of crossing vessels and gender, as well as kidney stones. Recurrence noted in 1 patient (2.78%) managed with redo laparoscopic pyeloplasty. Laparoscopic pyeloplasty is safe, effective option for treatment of PUJO with comparable success rate, less post operative pain, short hospital stay however operative duration is prolonged.